PENGARUH PENAMBAHAN TEPUNG KUNING TELUR DAN KRIMER NABATI TERHADAP MUTU TEPUNG PUDING INSTAN (The Effect of The Addition of Egg Yolk Flour and Non Dairy Creamer on The Quality of Instant Pudding Flour) - Putri Permatasari Marbun; Herla Rusmarilin; Elisa Julianti (Universitas Sumatera Utara, 2018)
ABSTRACT The purpose of the study were to determine the manufacture of egg yolk flour on a laboratory scale, to determine the effect of the addition of egg yolk flour and non dairy creamer, and interaction of egg yolk flour and non dairy creamer on instant pudding flour. This research used completely randomized design with two factors i.e. the addition of egg yolk flour (K) : (0%, 10%, 20%) and addition of non dairy creamer (S) : (0%, 25%, 50%, 75%, 100%). The parameters analyzed were moisture content, ash content, protein content, fat content, carbohydrate content, hedonic value of colour, aroma, flavor, and texture, overall acceptability, and gel strength was tested on the best treatment. The results showed that the addition of egg yolk flour gave highly significant effect on the moisture content, ash content, protein content, fat content, carbohydrate content, hedonic value of color of instant pudding flour, color of pudding, texture of pudding, and sineresis. The addition of non dairy creamer gave highly significant effect on the moisture content, protein content, fat content, carbohydrate content, color of instant pudding flour, color of pudding, flavor of pudding, texture of pudding, and sineresis. Interaction of the two factors had highly significant effect on fat content, carbohydrate content, color of instant pudding flour, color of pudding, texture of pudding, and sineresis. The addition of egg yolk flour of 20% and the addition of non dairy creamer of 75% was the best and acceptable treatment. Keywords: Egg Yolk Flour, Non Dairy Creamer, Instant Pudding Flour ABSTRAK Penelitian ini bertujuan untuk mengetahui cara pembuatan tepung kuning telur skala laboratorium, mengetahui pengaruh penambahan tepung kuning telur, penambahan krimer nabati, dan interaksi penambahan tepung kuning telur dan krimer nabati terhadap tepung puding instan. Penelitian ini menggunakan metode rancangan acak lengkap dengan dua faktor yaitu penambahan tepung kuning telur (K) : (0%, 10%, 20%) dan penambahan krimer nabati(S) : (0%, 25%, 50%, 75%, 100%). Parameter yang dianalisis adalah kadar air, kadar abu, kadar protein, kadar lemak, kadar karbohidrat, nilai hedonik warna, aroma, rasa, dan tekstur, penerimaan umum, sineresis, dan pada perlakuan terbaik dilakukan uji kekuatan gel. Hasil penelitian menunjukkan bahwa penambahan tepung kuning telur memberikan pengaruh berbeda sangat nyata terhadap kadar air, kadar abu, kadar protein, kadar lemak, kadar karbohidrat, nilai hedonik warna tepung puding instan, nilai hedonik warna puding, nilai hedonik tekstur puding, dan sineresis puding. Penambahan krimer nabati memberikan pengaruh berbeda sangat nyata terhadap kadar air, kadar protein, kadar lemak, kadar karbohidrat, nilai hedonik warna tepung puding instan, nilai hedonik warna puding, nilai hedonik rasa puding, nilai hedonik tekstur puding, dan sineresis puding. Interaksi kedua faktor tersebut memberikan pengaruh berbeda sangat nyata terhadap kadar lemak, kadar karbohidrat, nilai hedonik warna tepung puding instan, nilai hedonik warna puding, nilai hedonik tekstur puding, dan sineresis puding. Penambahan tepung kuning telur 20% dan penambahan krimer nabati 75% adalah perlakuan terbaik dan dapat diterima. Kata kunci : Krimer Nabati, Tepung Kuning Telur, Tepung Puding Instan